Role of virtual reality and active video games in motor and executive functions in cerebral palsy: a systematic review - Asifa Qurat Ul Ain; Arooj Fatima; Faraya Yousaf; Filza Shoukat; kashif Siddiqui; Ashfaq Ahmed (Journal of the Pakistan Medical Association, 2022)
Objective: To explore current evidence on the role of virtual reality and active video games in motor and executive functions compared to conventional physical therapies in cerebral palsy patients. Method: The systematic review was conducted at the University Institute of Physical Therapy, Lahore, Pakistan, and comprised search on MEDLINE via PubMed, Pedro and Cochrane Central related to randomised and clinical controlled trials published from 2005 to 2020. For critical appraisal of the studies, the Pedro tool was used, while methodological quality assessment was done using the Cochrane risk of bias tool. Results: Of the 15 articles reviewed, 14(93.3%) reported significant effect of virtual reality and active video games on motor functions. Critical appraisal found the quality of the studies from fair to high. Low risk was found in 4(26.7%) articles in terms of selection, 3(20%) allocation, 6(40%) detection, and 8(53.3%) had attrition bias. Unclear risk was reported in the performance and reporting bias domain in all the 15(100%) articles. Conclusion: Virtual reality games cannot be used as a substitute for therapy, but along with the conventional physical therapy, they are very effective and produce significant changes in motor functions in cerebral palsy patients. As for executive functions, more research needs to be done to determine the impact of these games at a higher level of brain. Key Words: Virtual reality therapy, Active video games, Motor rehabilitation, Executive functions.